ON THE PEDAGOGICAL FEATURES OF IMPROVING THE LANGUAGE COMPETENCE OF A FUTURE TEACHER-PHILOLOGIST (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
The article talks about the pedagogical features of increasing the linguistic competence of a future philology student, the problems of supporting the natural interests of students, interest in independent learning and supporting changes in solving language problems, taking measures to study the personal significance of complex linguistic competence.